Price Discrimination in Input Markets: Quantity Discounts and Private Information - Daniel Müller; Fabian Herweg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We consider a monopolistic supplier's optimal choice of wholesale tariffs when downstream firms are privately informed about their retail costs. Under discriminatory pricing, downstream firms that differ in their ex ante distribution of retail costs are offered different tariffs. Under uniform pricing, the same wholesale tariff is offered to all downstream firms. In contrast to the extant literature on price discrimination with nonlinear wholesale tariffs, we find that banning discriminatory wholesale contracts often improves welfare. This also holds if the manufacturer is not an unconstrained monopolist. Moreover, uniform pricing increases downstream investments in cost reduction in the long run.
Keywords: D43; L11; L42; 330